PENGUKURAN DAYA SAING KABUPATEN LAMPUNG TENGAH: METODE LOCATION QUOTIENT DAN SHIFT-SHARE ANALYSIS - Yanuar Pribadi (Balitbangda Provinsi Lampung, 2021)
This study aims to identify the leading sector economy and competitiveness of Central Lampung Regency, Lampung Province. The regency as an agricultural area is still classified as having very poor regional financial and fiscal capacity. Descriptive quantitative analysis using the Location Quotient and Shift-share Analysis methods were used to identify the basis of the economic sector and regional competitiveness. The results showed that there were only three leading economic sectors based on the LQ and DLQ methods in the economy of Central Lampung Regency, from Agriculture, Forestry and Fisheries, Construction and Manufacturing Industries. The shift-share analysis concludes that only two economic sectors in Central Lampung Regency are growing rapidly and have competitiveness in the 2016-2020 period, namely Transportation and Warehousing and Information and Communication. The results of the study could become an input for policymakers in designing economic development strategies for Central Lampung Regency to improve the regional economy.